Pentingnya Peran Logo dalam Membangun Brand - Oscario, Angela (Humaniora, 2013)
Brand is an intangible asset of an entity. It’s a summary of experiences of an entity. Well-developed brand is a very high value asset, even higher than all of the physical assets owned by the entity. Because brand is created on people’s mind, brand can build customer’s loyalty. Brand can be built in many ways. One of the most important way is designing visual indentity, such as logo. Logo is a graphical element in the form of ideogram, symbol, emblem, icon, sign that is collectively form a trademark or commercial brand. Logo is the entrance that reflects a brand. Because of that, a logo must reflect the soul of the entity. Considering how important a logo for a brand, a logo should be designed seriously. Ironically, there’re so many fast, and cheap logo design services that create an instant logo. Why is it happened? It’s because the brand owners have a lack of awareness of the important of a brand and a logo. It’s also because there are a lot of designers who have no respect on their profession. These kind of designers offer cheap services for an easy money with a little work. This situation can be bad for both of the brand owner and the designer. The price of logo design will be cheaper and cheaper, and the brand will not be developed well. That’s why it’s important to raise the awareness of the importance of a branding and a well designed logo which represent the soul of the entity.